The Role of Business Etchics as Moderating Variable in the Effect of Integrated Reporting, Corporate Social Responsibility, and Environmental Performance toward Corporate Reputation - Simandjuntak, JBP; Sudibyo, Yvonne (Archives of Business Research, 2022)
The study to analyze the effect of Integrated Reporting, Corporate Social Responsibility, and Environmental Performance toward Corporate Reputation. And also analyzes the impact of Business Ethics as a moderating variable that strengthens or weakens the relationship between the effects of Integrated Reporting, Corporate Social Responsibility, and Environmental Performance toward Corporate Reputation. The researcher collects empirical study data from the companies using secondary data taken from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) and Publish the Sustaninability Reporting. Then analyzes them using the Statistical Package for the Social Sciences. A total of 150 units of data analysis that meet the criteria and can be used as samples in this study. Business Etchics as a moderator between Integrated Reporting, Corporate Social Responsibility, and Environmental Performance toward Corporate Reputation with proxy and measurement on Corporate Coode of Conduct in companies listed on the Indonesia Stock Exchange is still little researched. So this research will not only fill in the current gaps in the literature but also spark new academic debates, but this study will also contribute to the practice of Corporate Reputation. This study reveals that Integreted Reporting and Environmental Performance have a positive and significant effect on Corporate Reputation. Corporate Social Responsibility have no effect on Corporate Reputation. Meanwhile, the role of the Business Ethics as a moderating variable have strengthens the influence between Integreted Reporting and Environmental Performance on Corporate Reputation from before being moderated by the Business Ethics. This study only takes secondary data from the annual reports of companies and Sustanainability reports of companies from the Indonesian stock exchange. And only have thirty companies as a data this study.